The comparison of pH sensing performance based on different polymer materials of TiO₂- based electrode - Mohd Masri, Aina Syakirah; Kamarozaman, Nur Syahirah; Zainal, Nurbaya; Zulkifli, Zurita; Herman, Sukreen Hana (UiTM Press, 2025)
This paper discussed on the comparison of pH sensor performance with different types of polyaniline (PANI) polymers as the TiO₂ composite sensing electrode material. Two types of PANI polymer were employed in this experiment which known as PANI emeraldine base (EB) and emeraldine salt (ES). By incorporating PANI into the sensing layer, the conductivity, stability, and sensitivity of the overall sensor performance can be enhanced. The digital microscopy revealed TiO₂-PANI EB’s superior uniformity and dispersion compared to TiO₂-PANI ES, which exhibited undissolved regions, indicative of their distinct solubility behaviours. FESEM analysis further exhibited identical surface morphology for both samples. TiO₂-PANI EB’s shows an excellent electrochemical sensing electrode with hydrophobic properties measured by contact angle 92.70°. EDX analysis showed that TiO₂- PANI EB had a higher content of PANI material, resulting in higher conductivity and superior sensor response. TiO₂-PANI EB’s Nernst response exhibited higher sensitivity and linearity (57.10 mV/pH, 0.9995) compared to TiO₂- PANI ES (46.24 mV/pH, 0.9963). These findings underscore the critical impact of polymer selection on the interfacial properties and overall functionality of TiO₂-PANI-based films pH sensors, providing significant insights for advancing sensor technologies in various applications.